2020
DOI: 10.3390/molecules25133008
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification of Surfactant on Oil Droplets by Molecular Dynamics Simulation

Abstract: Heavy oil in crude oil flooding is extremely difficult to extract due to its high viscosity and poor fluidity. In this paper, molecular dynamics simulation was used to study the emulsification behavior of sodium dodecyl sulfonate (SDSn) micelles on heavy oil droplets composed of asphaltenes (ASP) at the molecular level. Some analyzed techniques were used including root mean square displacement, hydrophile-hydrophobic area of an oil droplet, potential of mean force, and the number of hydrogen bonds between oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…This calculation was carried out using eq . where N is the number of atoms of the asphaltene molecules, r i ( t ) describes the position of the atoms at each simulation time, and r i (0) is the initial position. In addition, this calculation allows us to estimate viscosity differences since high RMSD values indicate that asphaltene molecules are displaced more This greater displacement results in lower internal friction and, therefore, lower viscosity. ,, …”
Section: Molecular Dynamics Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This calculation was carried out using eq . where N is the number of atoms of the asphaltene molecules, r i ( t ) describes the position of the atoms at each simulation time, and r i (0) is the initial position. In addition, this calculation allows us to estimate viscosity differences since high RMSD values indicate that asphaltene molecules are displaced more This greater displacement results in lower internal friction and, therefore, lower viscosity. ,, …”
Section: Molecular Dynamics Methodsmentioning
confidence: 99%
“…In addition, this calculation allows us to estimate viscosity differences since high RMSD values indicate that asphaltene molecules are displaced more This greater displacement results in lower internal friction and, therefore, lower viscosity. 56,59,60 The third evaluation parameter corresponds to the calculation of the asphaltene−asphaltene and asphaltene− solvent interaction energies. These calculations were conducted by defining two groups of atoms: those within asphaltene molecules and those of solvent molecules.…”
Section: Molecular Dynamics Methodsmentioning
confidence: 99%
“…Surfaktan merupakan senyawa organik yang banyak digunakan untuk keperluan rumah tangga dan industri, terutama sebagai deterjen dalam bahan pembersih (Riyanto, 2014). Selain itu surfaktan banyak digunakan sebagai agen flokulasi dan wetting (Mańko, 2017), perekat (Bondarchuk, 2017) dan pengemulsi (Cheng, 2020) dan dalam industri minyak dan gas (Pal, 2016;Massarweh, 2020). Hal ini dikarenakan surfaktan memiliki sifat yang unik dari struktur molekulnya yaitu mampu menurunkan tegangan antarmuka dan membentuk misel (Babajanzadeh, 2019) sehingga memungkinkan partikel-partikel yang menempel pada bahan-bahan yang dicuci terlepas dan mengapung terlarut dalam air.…”
Section: Pendahuluanunclassified
“…Subsequently, Baaden et al , reported the microscopic behavior of tributyl phosphate at the oil–water interface based on molecular dynamics simulation. In recent years, scholars such as Yuan and Hu , have also continually reported many molecular dynamics simulation studies on the adsorption and aggregation of surfactants at the oil–water interface. However, most of the current studies have the limitation of single model components.…”
Section: Introductionmentioning
confidence: 99%